Case report: Facilitating right heart recovery after durable LVAD implantation through repair of atrioventricular valves and RVAD implantation using tunneled Dacron grafts - Jones-Ungerleider, K. Candis; Raza, Syed Sikandar; Tang, Paul C. (Frontiers in Cardiovascular Medicine, 2023)
RVAD weaning is often an important goal for durable LVAD support. This may be facilitated by mitral and tricuspid repair as well as minimizing the trauma of RVAD decannulation by using dacron grafts.